Grafizacja w prasie, czyli o kilku przykładach organizacji przestrzennej tekstów prasowych - Ślawska, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
In the article, the author underlines that each press text is a macrostructure, organized by key elements (for example: titles, leads, initial and final fragments, photographs). Those elements in the press are isolated and graphically designed by authors and editors. The author considers the graphic shape of the text as a certain form of its visualization. In the article, the author refers to several texts from “Duży Format” (a supplement to the “Gazeta Wyborcza” daily), where textual space is visualized in various manners. The author points out multi-voice structures, the atypical lay-out of press columns in the fashion of photographs, introduction of infographics into reports, playing with light, or incorporating the text into the graphics. The represented examples of text graphization fit into the tendency of visual journalism, and at the same time prompt the viewer with additional possibilities for the interpretation of press texts.